2018
DOI: 10.1155/2018/7498514
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a Regulates Multidrug Resistance via Positively Modulating OAZ2 Signaling in Colon Cancer Cells

Abstract: Although aberrant expression of miR-34a, an essential tumor suppressor miRNA, has been frequently observed in colon cancer (CCa), whether miR-34a can regulate CCa progression by modulating other facets of this malignancy (such as multidrug resistance, MDR) remains unknown. Here, we report for the first time that miR-34a expression was significantly downregulated in clinical CCa samples from oxaliplatin-resistant patients and in experimentally established multidrug-resistant CCa cells. By using histoculture dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…qRT-PCR assay showed that overexpression of miR-154 and miR-34a suppressed circDENND2A levels ( Figure 5A). Previous reports revealed that miR-34a was a tumor inhibitor and that its expression was weak in numerous cancers (Li et al, 2018;Haghi et al, 2019;Luo et al, 2019). Our data verified that miR-34a level was down-regulated in NSCLC tissues (Figure 5B).…”
Section: Circdennd2a Sponged Mir-34a and Induced Ccne1 Expressionsupporting
confidence: 88%
“…qRT-PCR assay showed that overexpression of miR-154 and miR-34a suppressed circDENND2A levels ( Figure 5A). Previous reports revealed that miR-34a was a tumor inhibitor and that its expression was weak in numerous cancers (Li et al, 2018;Haghi et al, 2019;Luo et al, 2019). Our data verified that miR-34a level was down-regulated in NSCLC tissues (Figure 5B).…”
Section: Circdennd2a Sponged Mir-34a and Induced Ccne1 Expressionsupporting
confidence: 88%
“…For example, in the 5-FU-resistant cell line DLD-1/5-FU, mature miR-34a transfection attenuated 5-FU resistance and inhibited growth in the parental cells 38. MiR-34a decreased multidrug resistance and inhibited migration and invasion in colon cancer cells 39,40. However, in several studies, miR-34a has also been shown to function by enhancing chemoresistance 37.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a is a tumor suppressor miRNA: In colorectal cancer its expression is usually downregulated, often because of TGF-β action or long non-coding RNA acting as sponge for the miRNA [195,196]. Key features of miR-34a are the inhibition of cell migration and its chemosensitizer role in colorectal cancer [197,198]. COUP-TFII directly induces the expression of miR-21 in TGF-β-treated cells, resulting in the downregulation of SMAD7 whereas it reduces miR-34a [161,162]; hence, modulating miR-21a and miR-34a, COUP-TFII strengthen its action as tumor oncogene and induces EMT in colorectal cancer.…”
Section: The Gastrointestinal Cancers: Mostly An Oncogenementioning
confidence: 99%